Sex education of married women based on theory of planned behavior - Zeinab Jalambadani; Gholamreza Garmarodi; Mahmood Tavousi (Wolters Kluwer Medknow Publications, 2017)
Background: More than half of the sexual problems which cause life destruction and marital relationships are due to insufficient knowledge or false beliefs about sexual relationships. Theory of planned behavior (TPB) is one of the important theories that explain the main process of adopting health behaviors. This study investigates sex education based on TPB in married women visitors to Mashhad health-care centers in Iran. Materials and Methods: In this quasi-experimental study, 80 women visiting health centers of Mashhad city were studied, selected from 5 health centers by random-cluster method. Methods and data collection tool were the questionnaire which completed through the interview. The validity and reliability of this questionnaire were determined through face and content validity and through Cronbach's alpha and test-retest, respectively. Statistical Analysis Used: Data were analyzed using statistical SPSS (22) software, Spearman's correlation coefficient tests, and linear regression analysis. Results: In linear regression analysis, it was determined that attitudes, subjective norms, and perceived behavioral control (PBC) predict 0.45 overall of total variance of sexual function intention, which among these variables, the effect of subjective norms was more than the other ones (P value < 0.05). After educational intervention, the average rates of knowledge, attitude, PBC, and intention to sexual function in sex education group were increased meaningfully (P value < 0.05); these changes were not meaningful in control group. There was also no statistically meaningful difference in subjective norms between two groups after intervention. Conclusion: According to findings, it is proposed that TPB be used to improve sex education.